Når eksplosioner er kunst: Hatakeyama Naoyas idé om fotografer som latente kunstnere - Kloster Poulsen, Steffen (Periskop – Forum for kunsthistorisk debat, 2024)
This article argues for an expanded effort to search for, and actively utilize, concepts and methods from the sociolinguistic periphery of the otherwise anglocentric academic lit- erature on photography in order to achieve a more level playing field between vernacular concepts and purportedly universal ones. Taking the history of public debate on photo- graphy in Japan as a departure point, this article aims to map out a new area of explora- tion for photographic research in the academic field of art history. Japan has been home to a vivid public and intellectual debate on photography since the birth of photography and, although its output of photographers and photobooks has been globally acclaimed and exported to museums and galleries internationally, especially in the past thirty years, lit- tle emphasis in academic research and elsewhere has been put on Japanese photographic critique, theory and debate outside the archipelago. As an example of unexplored theory, this article analyzes two published lectures by Japanese photographer Hatakeyama Naoya in which he reflects on photography’s value as art, its place in the art world and the processes by which photographers become labelled as artists. Using a metaphor from analogue photography, he deems photographers “latent artists” who by a development process can become artists. Following Hatakeyama’s line of thought, this article argues furthermore that the metaphor can be extended to photographs themselves.